PENGEMBANGAN LKPD BERBASIS PENDEKATAN KONTEKSTUAL UNTUK MEMFASILITASI KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK SMP/MTs - Desnani Ulfa; Elfis Suanto; Putri Yuanita (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Penelitian ini dilatarbelakangi oleh rendahnya kemampuan koneksi matematis peserta didik dalam materi segiempat dan segitiga disebabkan bahan ajar yang belum dapat memfasilitasi kemampuan koneksi matematis. Penelitian bertujuan untuk menghasilkan LKPD berbasis pendekatan kontekstual pada materi segiempat dan segitiga untuk memfasilitasi kemampuan koneksi matematis peserta didik SMP/MTs. Metode penelelitian menggunakan 4D yaitu Define (pendefinisian), Design (perencanaan), Develop (pengembangan) dan Disseminate (penyebaran). Teknik pengumpulan data yang digunakan meliputi angket, observasi dan wawancara. Penelitian ini melibatkan peserta didik kelas VII SMP Negeri 3 Bangkinang. Hasil penelitian menunjukkan bahwa LKPD valid dari hasil expert review dan praktis dari hasil small group. Pada tahap small group LKPD yang dikembangkan memenuhi aspek penilaian yaitu: kemudahan penggunaannya, penyajian LKPD, keterbacaan, dan waktu. Sehingga LKPD berbasis pendekatan kontekstual untuk memfasilitasi kemampuan koneksi matematis bisa digunakan dalam pembelajaran.Kata kunci: Kemampuan Koneksi Matematis; LKPD; Pendekatan Kontekstual.This research is motivated by the low mathematical connection abilities of students in quadrilateral and triangle material due to teaching materials that cannot facilitate mathematical connection abilities. The research aims to produce LKPD based on a contextual approach to quadrilateral and triangle material to facilitate the mathematical connection abilities of SMP/MTs students. The research method uses 4D namely Define, Design, Develop and Disseminate. Data collection techniques used include questionnaires, observation and interviews. This research involved students of class VII SMP Negeri 3 Bangkinang. The results of the study show that LKPD is valid from the results of expert reviews and practical results from small group results. At the small group stage the developed LKPD meets the assessment aspects, namely: ease of use, presentation of LKPD, readability, and time. So that LKPD based on a contextual approach to facilitate mathematical connection abilities can be used in learning.Keywords:Contextual Approach; LKPD; Mathematical Connection CapabilityThis research is motivated by the low mathematical connection abilities of students in quadrilateral and triangle material due to teaching materials that cannot facilitate mathematical connection abilities. The research aims to produce LKPD based on a contextual approach to quadrilateral and triangle material to facilitate the mathematical connection abilities of SMP/MTs students. The research method uses 4D namely Define, Design, Develop and Disseminate. Data collection techniques used include questionnaires, observation and interviews. This research involved students of class VII SMP Negeri 3 Bangkinang. The results of the study show that LKPD is valid from the results of expert reviews and practical results from small group results. At the small group stage the developed LKPD meets the assessment aspects, namely: ease of use, presentation of LKPD, readability, and time. So that LKPD based on a contextual approach to facilitate mathematical connection abilities can be used in learning.Keywords: Contextual Approach; LKPD; Mathematical Connection Capability.